MANAGEMENT OF INVESTMENT RISKS IN THE SYSTEM OF PROJECT FINANCING (INNOVATIVE ECONOMY, 2019)
Yasinovska I.F., Sheremeta O.V. MANAGEMENT OF INVESTMENT RISKS IN THE SYSTEM OF PROJECT FINANCINGPurpose. The aim of the article is to investigate the problem of investment risk management in the project financing system.Methodology of research. The methodological basis of the study is the dialectical method of scientific knowledge. General scientific and special methods are used in the process of research, namely: abstract and logical, deductive and system analyzes – in the study of the peculiarities of project financing implementation; problems of management of investment risks in the project financing system; substantiation of ways of activation of development of project financing in Ukraine.Findings. A literary review and analysis of modern approaches to defining the concept of “project financing” have been carried out. The problematic aspects of the development of project financing in Ukraine are identified and the most common instruments for neutralizing investment risks in project financing are analyzed. According to official statistics, a significant proportion of business entities are found to be operating at a loss or low level of profitability, which negatively affects their creditworthiness and limits access to bank lending.In such circumstances, an important way out of this situation is to activate the development of project financing. Project financing, taking into account investment risks, can be provided by reliable financially sound banks, which have effective risk management, long-term resources, highly qualified specialists in financial investment analysis and consulting.Originality. The reasons for insufficient distribution of project financing in the banking sector of Ukraine have been identified and the directions of its activation have been proposed.Practical value. The findings of the study, which are expressed in the conclusions and proposals, contribute to solving the problem of improving investment risk management in project financing.Key words: project financing; project risks; investment risk; investment climate; investment risk management.
Keywords: Key words; project financing; project risks; investment risk; investment climate; investment risk management.